Minimal model for the magnetic phase diagram of CeTi1-xScxGe, GdFe1-xCoxSi, and related materials - Carreras Oropesa, W.G.; Encina, S.; Pedrazzini, P.; Correa, V.F.; Sereni, J.G.; Vildosola, V.; García D.J.; Cornaglia, P.S.; Sereni, Julián; Correa, Víctor Félix; Pedrazzini, Pablo (Elsevier, 2020)
Fil: Carreras Oropesa, William G. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidade de São Paulo. Instituto de Física; Brasil